Land Cover Changes on Ambergris Caye, Belize: A Case Study of Unregulated Tourism Development. Issue 1 (2nd January 2019) - Sweetman, Brenna M.; Cissell, Jordan R.; Rhine, Sandra; Steinberg, Michael K.
Abstract : Measuring land-use, land-cover change in biodiverse, tropical countries is critical for conservation management and sustainable planning because it provides quantifiable data regarding broad environmental changes. This project uses Landsat satellite imagery to document vegetation cover change on Ambergris Caye, Belize, from 2000 to 2017. The close proximity of the Belize Barrier Reef Reserve System has made Ambergris Caye the most popular tourist destination and economic hub in Belize. As a result, the region has undergone intense commercial and residential development coupled with rapid population growth over the past two decades. Understanding general trends in landscape dynamics is critical for the natural resource–based tourism industry of Belize to continue to thrive. Unsupervised classification methods and a per pixel postclassification comparison were used with Landsat imagery to estimate loss in vegetation cover and increases in urban and barren land. The results indicate a 10.85 percent decrease in vegetation and a 39 percent increase in urban and barren land during the seventeen-year study period with an annual forest loss rate of 0.67 percent per year using a compound interest rate formula. The results of this analysis represent a baseline study of vegetation change on Ambergris Caye to inform management and conservation efforts.